MMN and P3a elicited by a novelty paradigm in healthy controls: An investigation of sex differences. (11th June 2022) - Riel, Hayley; MacPhee, Catrina; Rudolph, Erica D.; Tibbo, Philip G.; Fisher, Derek J.
Highlights: Biological sex is often overlooked or underreported in electrophysiological research. Research examining sex in MMN and P3a are limited and inconsistent. Our study found no significant sex differences in MMN and P3a. Novel stimuli, which is more representative of the natural environment than standard tones that are often implemented, was used to elicit MMN and P3a waveforms. Abstract: The mismatch negativity (MMN) and P3a waveforms are both markers of auditory change detection. MMN indicates deficits in performing auditory change-detection tasks, while the P3a reflects the evaluative and conscious aspect of orienting to the sound. Understanding the role biological sex has concerning these waveforms would provide insight into overall brain-based differences, but whether sex differences exist to such a degree that it can moderate the effect of auditory change detection is not certain. Thus, the purpose of this study was to examine potential sex differences in MMN and P3a elicited by a novelty paradigm in a healthy population. The results showed no significant differences between males and females. This study proves to be useful by adding to the limited literature on the topic and by providing a foundation of knowledge regarding sex differences in auditory change detection mechanisms within the population.